2006
DOI: 10.1073/pnas.0501720103
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin expression is regulated by abscisic acid response regulators and is involved in abscisic acid-mediated photoprotection

Abstract: Fibrillins are lipid-binding proteins of plastids that are induced under abiotic stress conditions. In response to environmental stress, plants generate abscisic acid (ABA) as an endogenous signal. We show that ABA treatment and fibrillin accumulation enhance the tolerance of photosystem II toward light stress-triggered photoinhibition in Arabidopsis. ABA induces fibrillin accumulation, and the ABA response regulators ABI1 and ABI2 regulate fibrillin expression. The abundance of fibrillin transcripts was speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 47 publications
(63 reference statements)
8
97
1
1
Order By: Relevance
“…FBN5 is a phylogenetically distant relative of other fibrillins in Arabidopsis (Singh and McNellis, 2011), and it localizes to the stroma, with a lower pI and lower hydrophobicity than the other fibrillins (Lundquist et al, 2012). Therefore, FBN5 may play different roles from those previously reported for the fibrillins that localize primarily to the plastoglobules (Trebst, 1978;Yang et al, 2006;Singh et al, 2010Singh et al, , 2012Youssef et al, 2010). Surprisingly, we found that FBN5 specifically interacts with two solanesyl diphosphate synthases, SPS1 and SPS2, in the chloroplasts.…”
Section: Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…FBN5 is a phylogenetically distant relative of other fibrillins in Arabidopsis (Singh and McNellis, 2011), and it localizes to the stroma, with a lower pI and lower hydrophobicity than the other fibrillins (Lundquist et al, 2012). Therefore, FBN5 may play different roles from those previously reported for the fibrillins that localize primarily to the plastoglobules (Trebst, 1978;Yang et al, 2006;Singh et al, 2010Singh et al, , 2012Youssef et al, 2010). Surprisingly, we found that FBN5 specifically interacts with two solanesyl diphosphate synthases, SPS1 and SPS2, in the chloroplasts.…”
Section: Introductioncontrasting
confidence: 48%
“…Recently, fibrillin mutants of Arabidopsis have extended our understanding of the functions of the fibrillin proteins. The Arabidopsis FIBRILLIN1 (FBN1) gene family is involved in abscisic acid-mediated protection from photoinhibition (Yang et al, 2006), and the FBN1 and FBN2 gene families modulate jasmonate biosynthesis during light and cold stress (Youssef et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the interaction between FsPP2C1 and PYL7/RCAR2 and PYL5/RCAR8 is also present mostly in the nucleus. It is noteworthy that most of the targets previously identified for clade A PP2Cs were not nuclear proteins (Cherel et al, 2002;Guo et al, 2002;Ohta et al, 2003;Miao et al, 2006;Yang et al, 2006;Yoshida et al, 2006a). However, it is supposed that the interaction of ABI1 with the transcription factor ATHB6 must be nuclear (Himmelbach et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Values are means ± SDs of four replicates. Yeast two-hybrid tests were carried out for analysis of receptorcoreceptor interaction as described (3). HAB1 (AT1G72770), HAB2 (AT1G17550), PP2CA (AT3G11410), HAI1 (AT5G59220), HAI2 (AT1G07430), HAI3 (AT2G29380), AHG3 (AT3G11410), and PP2CE (AT5G27930) were amplified from a cDNA library as mentioned (8), cloned into the pGAD vector (Clontech), and expressed as activation domain fusion proteins.…”
Section: Methodsmentioning
confidence: 99%
“…ABA accumulates in response to water deficit and triggers rapid physiological responses for homeostasis of plants' water status. The immediate response includes stomatal closure to limit transpiration and initiation of adaptive gene expression (1,2), including protection of the photosynthetic machinery (3). ABA perception occurs by soluble ABA receptors acting in concert with protein phosphatases 2C (PP2Cs) of clade A (1,(4)(5)(6).…”
mentioning
confidence: 99%